Transcriptional activation by the orphan nuclear receptor ARP-1. - Malik, S (1995)
ARP-1 is a ubiquitous orphan nuclear receptor that binds to a site (site A) in the apolipoprotein AI (apoAI) liver-specific enhancer and represses its transcriptional activity in hepatoblastoma HepG2 cells. Electrophoretic mobility shift analysis of HepG2 cell nuclear extracts showed that in addition to ARP-1, site A also binds the orphan nuclear receptors Ear-2 and HNF-4. In in vitro transcription assays, Hela cell nuclear extracts which contain ARP-1 had no effect on transcription from a basal promoter linked to multiple copies of site A. However, supplementation of these extracts with excess amounts of recombinant ARP-1 resulted in significant stimulation. Supplementation of the extracts with purified polypeptides representing fusions between the ARP-1 N- or C-terminal domains and the yeast activator GAL4 DNA binding domain also stimulated transcription from a basal promoter linked to multiple GAL4 DNA binding sites. Co-immunoprecipitation assays using ARP-1-selective antibodies revealed specific physical interactions between ARP-1 and the basal transcription factor TFIIB. We conclude that ARP-1 possesses intrinsic transcription activation potential which is modulated, at least in part, by the intracellular balance of other nuclear receptors that also bind to its cognate DNA binding site.